Reducing Emissions, Forest Management and Multiactor Perspectives: Problem Representation Analysis of Laos REDD+ Programs - Herlin Chien (Forest and Society, 2019)
Every policy solution is embedded in a certain “problem representation” that is taken for granted and assumed by policymakers. This paper examines how emission reductions and forest management have been problematized for policymaking and solution implementation from multiple actors’ perspectives. Reducing Emissions from Deforestation and Forest Degradation (REDD+), particularly Forest Carbon Partnership Facility (FCPF) programs, in the Lao People’s Democratic Republic (Lao PDR) serves as a demonstrative example. By applying the ‘What is the Problem Represented to be’ (WPR) approach as a poststructuralist method, this study first comparatively analyzes the general problem as represented by multiple actors, including the government, media, academia and civil society. In particular, queries such as what and how the “problem” is represented and what is not problematized are reflected during the analyses. Next, this research further examines the corresponding problematization gap based on drivers of deforestation and forest degradation and discusses the noncarbon benefits of FCPF in the rhetoric. The objective of the study is to not to find the best policy choice but to reveal the heterogeneity in problem representations formulated by multiple actors to yield space for alternative and disruptive change for future problem solving in emission reductions and forest management